G421 The current causes and risk factors for sudi. (27th April 2015) - Garstang, J; Ellis, C; Sidebotham, P; Griffiths, F
Abstract : Aims: Since 2008, in England, all unexpected child deaths undergo a multi-agency investigation with the aim of determining the complete cause of death; followed by review by local Child Death Overview Panels (CDOP). These new processes have yet to be evaluated. This study aims to determine the effectiveness of the multi-agency investigation and CDOP processes in ascertaining causes of death and risk factors following Sudden Unexpected Death in Infancy (SUDI) and to describe the profile of causes and risk factors. Methods: We obtained the dates of birth and death of all SUDI cases from one English region, dying between 1 September 2010 and 31 August 2012. We contacted all 10 CDOP for copies of individual case reviews completed using the standard CDOP Form C. We extracted the age, cause of death and presence of modifiable factors for each case from the Form C and created a total family and environmental risk factor score by totalling the risk factors. Results: Data were obtained for 65/70 (93%) SUDI cases. 20/65 (31%) deaths were due to medical causes; 21/65 (32%) due to SIDS and 24/65 (37%) classified as unascertained deaths. Reanalysis of case data suggested that 9 deaths were probably due to accidental asphyxia, with 6 of these involving parents co-sleeping with their infant after consuming excessive alcohol. Unascertained deaths had significantly higher total family and environmental risk factor scores (mean 2.6, 95% CI 2.0–3.3) compared to SIDS (mean 1.6, 95% CI 1.2–1.9), or medical causes for death (mean 1.1, 95% CI 0.8–1.3). 9/20 (47%) of medical deaths. 19/21 (90%) SIDS and 23/24 (96%) unascertained deaths were considered to be preventable. There were inadequacies in medical provision identified in 5/20 (25%) of medically explained deaths. Conclusions: The new multi-agency child death processes are effective at determining cause of death and risk factors for SUDI but potential asphyxia deaths may not be recognised. Most deaths labelled as unascertained fulfilled diagnostic criteria for SIDS. Many SUDI occurred in families with mental illness, drug or alcohol misuse and chaotic lifestyles and most in unsafe sleep-environments.